2013
DOI: 10.1186/bcr3460
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic reversion of epigenetic silencing of the PRKD1promoter blocks breast tumor cell invasion and metastasis

Abstract: IntroductionDNA methylation-induced silencing of genes encoding tumor suppressors is common in many types of cancer, but little is known about how such epigenetic silencing can contribute to tumor metastasis. The PRKD1 gene encodes protein kinase D1 (PKD1), a serine/threonine kinase that is expressed in cells of the normal mammary gland, where it maintains the epithelial phenotype by preventing epithelial-to-mesenchymal transition.MethodsThe status of PRKD1 promoter methylation was analyzed by reduced represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 48 publications
4
123
0
Order By: Relevance
“…The low expression of PRKD1 in PC3 compared with AR-positive cell lines may be the explanation for its high motility. Epigenetic silencing of the PRKD1 promoter in PC3 cells could be a reason for the low expression, which was also shown for highly invasive breast cancer cell lines (Borges et al 2013). An inhibitory effect of PRKD1 on cellular proliferation could be explained by stimulation of secretion of matrix metalloproteinases-2 and -9 .…”
Section: Ncoa1 Regulates Various Cell Migration Pathwaysmentioning
confidence: 99%
“…The low expression of PRKD1 in PC3 compared with AR-positive cell lines may be the explanation for its high motility. Epigenetic silencing of the PRKD1 promoter in PC3 cells could be a reason for the low expression, which was also shown for highly invasive breast cancer cell lines (Borges et al 2013). An inhibitory effect of PRKD1 on cellular proliferation could be explained by stimulation of secretion of matrix metalloproteinases-2 and -9 .…”
Section: Ncoa1 Regulates Various Cell Migration Pathwaysmentioning
confidence: 99%
“…Curcumin suppresses multiple signaling pathways (58), such as caspase activation, induction of cell death receptors, aggregation of Fas receptors, induction of p53, and p21 pathways (57), release of apoptosis-inducing factor (57,60), regulation of the cell cycle (58,61), inhibition of PI3K-AKT activation, mTOR inhibition, downregulation of androgen receptors (57), inhibition of AMP-activated protein kinase, inhibition of COX2 and LOX 5, inhibition of STAT3 activation (57), c-Jun kinase activation, induction of DNA fragmentation, depletion of intracellular Ca 2 , mitochondrial activation, direct damage to the DNA, anti-apoptotic protein suppression, autophagy, antioxidant mechanisms, proteasome activation, NF-κβ inhibition, among others (58,61). Thus, many studies have focused on improving its clinical effectiveness by modifying its delivery system through nanotechnology (62,63).…”
Section: A) Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…b) Epigenetic changes. Epigenetic silencing of tumor suppressor genes such as TP53 or PKD1 that can influence the tumor microenvironment and promote the progression of a breast tumor to an aggressive metastatic phenotype (2,28,39). c) miRNA.…”
Section: A) Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Various studies have identified several genes that are frequently hypermethylated in OOSCC, 14,15 such as CDH1, CDKN2A, O-6-methylguanine-DNA methyltransferase (MGMT), death-associated protein kinase 1 (DAPK1), RARB, and RASSF1, but only few of those have been associated with metastasis. 16,17 In other cancers, various methylation markers have been associated with cell migration and invasion in vitro 18,19 and the presence of nodal metastasis. 19,20 In this study, we set out to identify novel methylation markers that are associated with the presence of lymph node metastases in patients with OOSCC.…”
Section: Introductionmentioning
confidence: 99%